Detection of bluetongue virus antigens in Culicoides variipennis by enzyme immunoassay. - el Hussein, A (1989)
A solid-phase enzyme immunoassay (EIA) was developed to detect bluetongue (BT) virus antigens in infected cell cultures and in suspensions of infected Culicoides variipennis midges. The technique was equally sensitive for detecting the five U.S. BT virus serotypes (2, 10, 11, 13, and 17) in cell cultures. EIA reliably detected about 3.8 log10 median tissue culture infective doses per ml of BT virus in infected cell culture lysates. The EIA readily detected virus antigens in pools of midges infected with BT serotypes 2, 10, 11, 13, and 17 and contained 2.3 to 4.8 log10 median tissue culture infective doses per ml of BT virus. The technique was sensitive enough to detect a single infected midge in a pool with 99 noninfected midges. The EIA may be a sensitive and rapid alternative to virus isolation for surveillance of BT viruses in vector populations.